The Power of Satisfaction: Mitigating Occupational Stress to Boost Teachers' Motivation - Ali Sulaiman Talib Al Shuaili (International Journal of Education and Humanities, 2025)
This study was conducted during the academic year 2023/2024 and explored the relationship between occupational stress, job satisfaction, and occupational motivation among Omani teachers, focusing on job satisfaction as a mediator. The aim was to identify strategies to enhance teachers' motivation and well-being within the Omani education system. The study focused on government schoolteachers in various Omani governorates, using a stratified random sample of 714 participants. A descriptive correlational design was used, with data collected through a validated questionnaire addressing occupational stress, job satisfaction, and occupational motivation, where validated scales from the literature were adopted. Statistical analyses included descriptive statistics, Pearson correlation, and regression analysis. The results showed a significant negative relationship between occupational stress and occupational motivation, with job satisfaction mitigating the adverse effects of stress. Teachers who reported higher satisfaction were better able to maintain motivation despite stress. It is worth noting that teachers and those with extensive teaching experience reported higher stress levels, but motivation was sustained when satisfaction was high. The study recommended introducing stress management initiatives, improving working conditions, and providing professional development opportunities to enhance job satisfaction and motivation. It has also urged policymakers to address systemic challenges and suggested further research to explore additional factors that influence these dynamics